2018
DOI: 10.1155/2018/8741249
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphic Variants of TNFR2 Gene in Schizophrenia and Its Interaction with -308G/A TNF-α Gene Polymorphism

Abstract: Aim Many data showed a role of inflammation and dysfunction of immune system as important factors in the risk of schizophrenia. The TNFR2 receptor is a molecule that adapts to both areas. Tumor necrosis factor receptor 2 (TNFR2) is a receptor for the TNF-α cytokine which is a strong candidate gene for schizophrenia. The serum level of TNFR2 was significantly increased in schizophrenia and associated with more severe symptoms of schizophrenia. Methods We examined the association of the three single nucleotide p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
(33 reference statements)
1
6
0
1
Order By: Relevance
“…Xiu et al ( 138 ) have suggested an important role for cytokine signaling in mediating the severity of cognitive dysfunction in schizophrenia and reported that the TNF-α 21031T/C polymorphism may not play a role in the predisposition of schizophrenia itself but may be implicated in the cognitive deficits of schizophrenia. In a case-control study, Suchanek-Raif et al ( 139 ) demonstrated that, for the TNFR2 gene, the genetic variants of rs3397, rs1061622, and rs1061624 are linked with a higher risk of developing schizophrenia and a more severe course in men. In contrast, the genotypes with a polymorphic allele for rs3397 SNP appear protective for women.…”
Section: Cytokine Polymorphisms In Schizophreniamentioning
confidence: 99%
“…Xiu et al ( 138 ) have suggested an important role for cytokine signaling in mediating the severity of cognitive dysfunction in schizophrenia and reported that the TNF-α 21031T/C polymorphism may not play a role in the predisposition of schizophrenia itself but may be implicated in the cognitive deficits of schizophrenia. In a case-control study, Suchanek-Raif et al ( 139 ) demonstrated that, for the TNFR2 gene, the genetic variants of rs3397, rs1061622, and rs1061624 are linked with a higher risk of developing schizophrenia and a more severe course in men. In contrast, the genotypes with a polymorphic allele for rs3397 SNP appear protective for women.…”
Section: Cytokine Polymorphisms In Schizophreniamentioning
confidence: 99%
“…Polymorphisms of TGFB1, which encodes TGF-β, along with its additional overexpression [70] were also associated with schizophrenia [71]. Quite remarkably, polymorphisms of the TNFR2 gene encoding the TNF-α receptor, depending on the variant, may be associated with an increased risk of schizophrenia, or may have a protective effect [72].…”
Section: Immunogenetics Of Cytokine Alternations In Schizophreniamentioning
confidence: 99%
“…(2014) Variant was associated with autism risk whereby G allele seems to have a protective effect rs1061624 TNFR2 Neuroinflammatory response; neurogenesis AG (heterozygous) Stacey et al. (2017) A allele was associated with decreased hippocampal grey matter volume, compared to GG genotype Suchanek-Raif et al. (2018) GA genotype associated with higher risk of schizophrenia among individuals with a family history of SZ …”
Section: Resultsmentioning
confidence: 99%
“…The cells were found to be heterozygous for the second SNP on the TNFR2 gene, rs1061624. Even though this genotype has been associated with an increased risk of developing Schizophrenia ( Suchanek-Raif et al., 2018 ), this was only true for subjects with a family history of the disease and such information is not available for the donor of the HPC0A07/03C cell line.…”
Section: Variants With Demonstrated Associations With the Risk Of Neurological Or Psychiatric Diseasesmentioning
confidence: 99%